2020
DOI: 10.1177/1120672120938575
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery in treated retinoblastoma eyes: A study of 29 eyes

Abstract: Purpose: To study the outcomes of cataract surgery in treated retinoblastoma (RB) eyes. Methods: Retrospective study of 29 eyes of 27 patients. Results: Based on International Classification of Intraocular Retinoblastoma, tumors belonged to group B ( n = 3, 10%), C ( n = 1, 4%), D ( n = 10, 34%), and E ( n = 3, 10%). The remaining 12 eyes (41%) had regressed tumors on presentation due to prior treatment. The RB treatment details included intravenous chemotherapy ( n = 24, 83%), external beam radiotherapy ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Main complications were a transient macular edema in 31% and an iridocyclitis in 19%. Recently a larger series was published by Kaliki et al [13] on results of cataract surgery and intraocular lens implantation through clear corneal incision in pediatric radiation-induced cataracts in 29 eyes of 27 retinoblastoma children. Improvement in visual acuity occurred in 55% of the treated eyes, with a mean follow-up of 103 months.…”
Section: Discussionmentioning
confidence: 99%
“…Main complications were a transient macular edema in 31% and an iridocyclitis in 19%. Recently a larger series was published by Kaliki et al [13] on results of cataract surgery and intraocular lens implantation through clear corneal incision in pediatric radiation-induced cataracts in 29 eyes of 27 retinoblastoma children. Improvement in visual acuity occurred in 55% of the treated eyes, with a mean follow-up of 103 months.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery outcomes in children treated for Rb have been largely reported for radiation-induced cataracts5 and cataracts consequent to direct or other biochemical effects of the tumour and local tumour therapy 1. With a revival of focus on IVitC for vitreous disease in Rb,3 an associated challenge of dealing with IVitC-induced cataracts has also surfaced.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular surgery in these eyes carries a risk of extraocular tumour spread that could be potentially lethal. In view of this risk, it is believed to be safe to ensure clinical regression of the intraocular tumour as best as possible before proceeding with cataract surgery 1. Tumour seeding of the vitreous humour within the eye can often be a difficult problem to treat as tumoricidal concentration of chemotherapeutic agents is difficult to achieve in the vitreous cavity 2.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 As for timing, the suggested quiescent time required to perform cataract surgery varies in different studies. 1,2,[5][6][7] Among these, the two earliest possible safety periods are outlined as 9 months by Osman et al 7 and time from tumor regression to cataract surgery has been reported as early as 6 months by Kaliki et al 6 However, earlier interventions may also be justified when tumor activity cannot properly be assessed. Miller et al 5 have suggested an interval period of at least 28 months if there was apparent vitreous or subretinal seeding any time during disease course.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There has been several reports on cataract surgery following radiotherapy for retinoblastoma with encouraging results for safety of cataract extraction when the surgery is performed in the presence of an inactive tumor. [3][4][5][6] However, management of cataracts presumably due to intravitreal chemotherapy injections when the intravitreal treatment still needs to be continued and when the status of the vitreal seeds can no longer be accurately assessed, has not been previously addressed to on its own. There is no consensus on the exact timing of the surgery or the precautionary steps to be taken intra-operatively in cataract removal from an eye with retinoblastoma associated with vitreous seeds.…”
Section: Introductionmentioning
confidence: 99%